Protons and Ca2+: ionic allies in tumor progression? - Glitsch, M (2011)
Ion channels and G-protein-coupled receptors (GPCRs) play a fundamental role in cancer progression by influencing Ca(2+) influx and signaling pathways in transformed cells. Transformed cells thrive in a hostile environment that is characterized by extracellular acidosis that promotes the pathological phenotype. The pathway(s) by which extracellular protons achieve this remain unclear. Here, a role for proton-sensing ion channels and GPCRs as mediators of the effects of extracellular protons in cancer cells is discussed.